Pollen characterization and male phase of Nipa (Nypa fruticans) stand in Davao Region. - Licup, Kristian Weller Peñanueva (2011)
The male phase, pollen viability and pollen characterization of Nypa fruticans, were studied through observation and experiments in wild stands at Bago Aplaya, Davao City (702?21? N, 125032?03? E, elevation: 21 m), Ecoland, Davao City (703?28? N, 125036?24? E, elevation: 19 m), Talomo, Davao City (702?52? N, 125033?26? E, elevation: 29 m), Purok 17, Carmen, Davao del Norte (7021?46? N, 125042?13? E, elevation: 23 m) and Brgy. Ising, Carmen, Davao del Norte (7021?47? N, 125042?33? E, elevation: 20 m). A total of 68 nipa inflorescences were observed over a 10-month period. Male flower anthesis occurred first on the upper region of the inflorescence followed by the middle region then lastly the lower region. It took 5 to 6 days from opening to drying out all staminate rachillae in each region, or an about 14 days for the whole male phase of a nipa plant. Staminate rachillae of a nipa had length of 5 to 7 cm and a count of 17 to 33 per plant with the stands in Carmen, Davao del Norte as significantly higher than those from Davao City. No significant differences between the pollen viabilities of the upper and lower region, but the middle region had significantly higher pollen viability than both regions. Overall, viability was estimated at 73.11%. Nipa pollen is characterized as non-angular circular with some samples elliptical in shape with no apertures found, echinae were visible on the exines, yellow in color and the inner parts of the pollens were visible on some samples